2005
DOI: 10.7863/jum.2005.24.2.143
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Optic Nerve Diameter in Children With Raised Intracranial Pressure

Abstract: Optic nerve diameter, measured by transorbital sonography, was significantly greater in pediatric patients with increased ICP compared with a control group. Transorbital sonography can be used to identify pediatric patients with raised ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 13 publications
3
67
0
5
Order By: Relevance
“…There was a significant positive correlation between ONSD and age established from their study. Similar finding was obtained in a study by Aschkan [22] on sonographic evaluation of optic nerve sheath diameter in children with raised intracranial pressure among the controls used. This is contrary to findings in this study, no significant correlation between ONSD and age was observed.…”
Section: Section: Radiologysupporting
confidence: 88%
“…There was a significant positive correlation between ONSD and age established from their study. Similar finding was obtained in a study by Aschkan [22] on sonographic evaluation of optic nerve sheath diameter in children with raised intracranial pressure among the controls used. This is contrary to findings in this study, no significant correlation between ONSD and age was observed.…”
Section: Section: Radiologysupporting
confidence: 88%
“…The upper limit of the normal range for optic nerve sheath diameter is 4.5mm in patients over 1 year of age, and 4mm in children younger than 1 year of age. [27][28][29] Newman et al 29 found that patients with functioning ventriculoperitoneal shunts had a mean optic nerve sheath diameter of 3mm, while those with raised ICP had a mean optic nerve sheath diameter of 5 to 6mm. Evaluation of optic nerve sheath diameter is a potentially useful tool in the assessment and monitoring of children with hydrocephalus suspected of having raised ICP.…”
Section: Neonatal Fontanelle Compressionmentioning
confidence: 99%
“…9 This non-invasive technique has been used successfully in emergency rooms, [10][11][12] children with hydrocephalus, 13 and children with other causes of raised ICP. 14 We have previously established normative values for ONS diameter in Malawian children and showed the use of ONS ultrasound for detecting raised ICP in a resource-poor setting. 15 That study suggested that an ONS diameter of 4.3 mm and above was abnormal and had a sensitivity and specificity of 100% and 86% for detecting raised ICP, respectively.…”
Section: Introductionmentioning
confidence: 99%